Lutetium oxide film as a passive saturable absorber for generating q-switched fiber laser at 1570 nm wavelength - Abdul Latiff, Anas; Baharom, Mohamad Faizal; Harun, Sulaiman Wadi; Arof, Hamzah; Ab Rahman, Mohd Fauzi; Wang, Pengfei (Academic Press Inc., 2019)
We report for the first time, the application of Lutetium oxide (Lu2O3) thin film as a saturable absorber (SA) in generating a stable and compact Q-switched Erbium-doped fiber laser (EDFL) operating at 1570 nm. The film SA was prepared by embedding the Lu2O3 particles into a polyvinyl alcohol (PVA) host film. By integrating the film SA in a laser cavity, a stable pulsed laser appeared when the input pump power hit the threshold at 26.3 mW. The frequency of the pulsed laser rose from 18.4 kHz to 30.4 kHz, matching the increase of pump power from 26.3 mW to 71.6 mW. The shortest pulse width of 8.47 µs and the highest peak power of 8.98 mW were obtained at the maximum available pump power of 71.6 mW. Meanwhile, the maximum output power and pulse energy were measured at approximately 2.32 mW and 76 nJ, respectively. In addition, the signal to noise ratio (SNR) was 40 dB. These indicators suggest that Lutetium oxide film is a good passive SA that can be used to generate pulsed laser operating at1.55 µm region.